LyeTx I-b Peptide Attenuates Tumor Burden and Metastasis in a Mouse 4T1 Breast Cancer Model - Mostafa A. L. Abdel-Salam; Bárbara Pinto; Geovanni Cassali; Lilian Bueno; Gabriela Pêgas; Fabrício Oliveira; Irismara Silva; André Klein; Elaine Maria de Souza-Fagundes; Maria Elena de Lima; Juliana Carvalho-Tavares (MDPI AG, 2021)
Cationic anticancer peptides have exhibited potent anti-proliferative and anti-inflammatory effects in neoplastic illness conditions. LyeTx I-b is a synthetic peptide derived from Lycosa erythrognatha spider venom that previously showed antibiotic activity in vitro and in vivo. This study focused on the effects of LyeTxI-b on a 4T1 mouse mammary carcinoma model. Mice with a palpable tumor in the left flank were subcutaneously or intratumorally injected with LyeTx I-b (5 mg/kg), which significantly decreased the tumor volume and metastatic nodules. Histological analyses showed a large necrotic area in treated primary tumors compared to the control. LyeTxI-b reduced tumor growth and lung metastasis in the 4T1 mouse mammary carcinoma model with no signs of toxicity in healthy or cancerous mice. The mechanism of action of LyeTx I-b on the 4T1 mouse mammary carcinoma model was evaluated in vitro and is associated with induction of apoptosis and cell proliferation inhibition. Furthermore, LyeTx I-b seems to be an efficient regulator of the 4T1 tumor microenvironment by modulating several cytokines, such as TGF-β, TNF-α, IL-1β, IL-6, and IL-10, in primary tumor and lung, spleen, and brain. LyeTx I-b also plays a role in leukocytes rolling and adhesion into spinal cord microcirculation and in the number of circulating leukocytes. These data suggest a potent antineoplastic efficacy ofLyeTx I-b.